The Mathematical Thinking Profiles Of Junior High School Students At SMP Negeri 1 Sukadana In Solving Higher Order Thinking Skills (HOTS) Problems On Statistics - sulastriani,; Fadillah Al - Hadad, Syarifah; Buchari, Buchari (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Abstract: Mathematical thinking is a critical cognitive skill that enables students to interpret, analyze, evaluate, and draw conclusions when solving mathematical problems, particularly those demanding higher-order reasoning. In statistics learning at the junior high school level, students commonly show considerable variation in their mathematical thinking processes, especially when interpreting statistical data and determining appropriate solving strategies for Higher Order Thinking Skills (HOTS) problems. This study aimed to analyze the mathematical thinking profile of eighth-grade students at SMP Negeri 1 Sukadana in solving HOTS problems on statistics, focusing on their ability to identify given and asked information, select relevant concepts or formulas, arrange systematic solution steps, and verify and conclude their answers. A qualitative descriptive method with a case study design was used. Data were collected through diagnostic tests and in-depth interviews with six students purposively selected from class VIII G, representing high, moderate, and low mathematical-ability categories (two students per category); the test instrument was validated by two mathematics education lecturers and one subject teacher, and data credibility was ensured through triangulation. The results showed distinct differences in mathematical thinking profiles across ability levels. High-ability students accurately identified problem information, selected correct concepts, constructed systematic and logical solution steps, and consistently verified their answers. Moderate-ability students understood most of the given information but had difficulty fully interpreting the problem and made minor procedural errors. Low-ability students frequently failed to identify complete information, applied incorrect concepts, made computational errors, and rarely re-checked their final answers. Overall, the findings indicate that the higher a student's mathematical ability, the more systematic and complete their thinking process in understanding, planning, executing, and evaluating solutions to statistics-based HOTS problems. These findings suggest that teachers should strengthen contextual, story-based problem practice, habituate systematic solution-writing, and emphasize answer-checking strategies to improve students' higher-order mathematical thinking in statistics..